Young Women in Foster Care: Social Support Capital as an Empowerment Resource against Gender-based Violence in Intimate Partners. - Foradada-Villar, Mireia; Sala-Roca, Josefina (Child & Adolescent Social Work Journal, 2026)
This research seeks to map perception of gender-based violence and social support capital and its impact on the position and coping strategies in these situations of a group of young women in foster care (FC) who have been mentored and a group of non-foster care undergraduate women (N-FC) who participated in a mentoring program on gender-based violence. The study also examines whether there are differences between the two groups. Using an intersectional mixed-methods approach, the research explores coping and prevention strategies among 29 FC and 30 N-FC participants. Data analysis combines first a thematic analysis (using Nvivo 12 software) for qualitative perspectives, and secondly frequency analysis and statistical measures to find a relationship between strategies and social support capital (via SPSS software). Findings emphasize that N-FC and FC are similarly tolerant of violence, though some N-FC tolerate more verbal violence. FC women's resilience to direct violence is clearly higher due to past experiences, but they have less social support capital, making it harder to leave toxic relationships. Indeed, FC women's lower social support capital is correlated with greater difficulty leaving toxic relationships. Despite this, for the first time the research identifies FCs' strategies to deal with gender-based violence, including education, silent resistance, confrontation, and the termination of the relationship. Again, FCs are more likely to use silent strategies to prevent partner violence and less likely to use confrontational strategies due to their social support capital. Participants use their gender capital to confront gender-based violence, balancing personal resources, agency, perceived danger, and social support. The findings highlight friends as the most crucial support source, suggesting that friends' role as a resource against gender-based violence warrants further research for FC.